Problem-solving courts and the criminal justice system - DeMatteo, David (Oxford clinical psychology, 2019)
Problem-Solving Courts and the Criminal Justice System provides professionals and students in the fields of mental health, criminal justice, law, and related fields with a comprehensive foundation of information related to problem-solving courts and the role such courts play in reforming the United States criminal justice system. The book is a timely response to the rapidly changing landscape of that system, relatively recent development of problem-solving courts, and the ongoing paradigm shift away from punishment and toward restorative justice.